THE ROLE OF LANDSCAPE IN A POETIC IMAGE - Jumakhoja, Nusratullo (International Journal of Psychosocial Rehabilitation, 2020)
The article specifically examines the aesthetic function of landscape as a means of poetic depiction in the poetry of the Uzbek poet Shermuhammad Munis (1778-1829). In classical gazelle creativity, the landscape performs basically two functions: 1. As an object or object of an artistic image, when the verses themselves are landscape. 2. As a means of poetic image, which, regardless of the specific content of the work, performs the aesthetic function of poetic material or images that contribute to the disclosure of the theme and idea.Munis showed high examples of the use of paintings of social life and nature as a means of poetic depiction, deepening the ideological content of a work, educating a person in the spirit of love for nature and life.Thus, each object or phenomenon of nature can be used as poetic material for the embodiment of the creative intent of the poet. Many artistic techniques in classical poetics are based on the use of the close connection of poetry with life, nature, and on the borrowing of means of artistic depiction from nature.